Curious children and knowledgeable adults – early childhood student-teachers’ species identification skills and their views on the importance of species knowledge - Skarstein, Tuula H.; Skarstein, Frode (International Journal of Science Education, 2020)
This study investigates early childhood (EC) student-teachers’ species identiﬁcation skills and their views on the importance of species knowledge. The study used a mixed methods approach, including a species identiﬁcation test and a questionnaire, and involved 186 Norwegian EC student-teachers. Our results reveal that species knowledge of ﬁrst-year students was poor when they entered university. During their ﬁrst semester, the students learn about common, local species and this knowledge seems to be maintained throughout their studies. The majority of the students had use of species knowledge during their practical training periods in kindergartens and considered species knowledge important for EC teachers as well as for sustainable development. The need for species knowledge was often associated with spontaneously occurring situations initiated by children during nature excursions. The students argued that species knowledge is important for fostering children’s curiosity, increasing their understanding of nature and strengthening their relationship with nature. We hope that this study can illustrate the importance of species knowledge in EC teacher education. It is essential that students acquire both the knowledge and skills to facilitate the variety of learning possibilities that exist in nature and are able to provide children possibilities to learn about the diversity of nature as well as to develop a relationship with it.